Greenhouse Gases and Determinants of Growth: An Analysis of the Environmental Kuznets Curve Hypothesis on ASEAN-5 Countries - Claire Daiynes Pama; Abigail Joy Pastrana; Jasmine Isabella Rogel; Marie Antoinette Rosete (UJoST- Universal Journal of Science and Technology, 2022)
The Environmental Kuznets Curve (EKC) hypothesis is the most notable method for measuring environmental degradation and its relationship with economic growth. In this research paper, the researchers examine the validity of the relationship between carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), and fluorinated gasses (F-Gas) to Gross Domestic Product, population, renewable energy consumption, trade openness, and inflation of the ASEAN-5 countries’ data from 1990-2018, using panel regression tests which are POLS, FE model, and RE model. Results reveal that the independent variables do not affect CH4 based on the RE model while CO2, N2O, and F-GAS are partially affected based on the FE model. The EKC is confirmed only for F-GAS, suggesting that a turning point is established. Other emissions imply that these economies are still in their early stages of development, hence the non-existence of EKC. Based on the outcomes, recommended actions specifically for the agricultural and industrial sectors include the following: (1) investing in renewable energy, (2) provision of subsidies and incentivization, and (3) adopting and modifying emission-related systematic waste management and recycling to better suit each countries’ economy.